The Use of Banana Corm Extract and Phosphate Rock to Increase Available-P in Alfisol - Slamet Minardi; Sri Hartati; Hery Widijanto; Defi Wulandari (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2015)
The aim of this research is to study the approprite formula and applied method of banana corm and phosphate rock on available-P in Alfisols. The research was arranged in factorial completely randomized design with 3 factors. The first factor is the dosage  of banana corm extract, which is consisted of: E1 = 100  ml of banana corm extract, E2 = 200 ml of banana corm extract, and E3 = 300 ml of banana corm extract. The second factor is the dosage of the phosphate rock which is consisted of B1 = 100 gr of  phosphate rock, B2 = 200 gr phosphate rock, and B3 = 300 gr of phosphate rock. The third factor is application method, which is consisted of M1 = directly applied  into the soil. M2 = incubated before applied into the soil. The observation of soil includes: soil pH, soil organic matter content, cation exchange capacity, total-N, total-P, available-P and the population of phosphate solubilizing bacteria. Result shows that available-P in the Alfisols is very low. The interaction amongs the treatment significantly affect the population of phosphate solubilizing bacteria. Banana corm extract and  phosphate rock applied directly into the soil increase soil pH.